Technology-based Formative Assessments Implemented by Secondary School English Teachers During Remote Learning - Fani Prastikawati, Entika; ., Wiyaka (KnE Social Sciences, 2022)
During the COVID-19 pandemic, teachers had to alter their assessment process for an engaging and productive remote learning. The present study investigates the technology-based formative assessments carried out by secondary school English teachers. To reach that goal, the writers conducted a series of observations and an interview. It was found that English teachers used a few technology-based formative assessment platforms such as Quizizz, Kahoot!, Schoology, Microsoft Office Team, and Socrative. Oral and written feedback was also regularly done by English teachers for supporting technology-based formative assessment practices. The finding of this study also implies the crucial role of digital literacy in supporting the successful implementation of technology-based formative assessments during distance learning. Keywords: technology-based formative assessment, English teaching and learning, remote learning